A STUDY OF THE IMPACT OF GROWING DISPOSABLE INCOME IN FAMILIES ON VACATIONS – IN CHENNAI CITY - M. Srividya Iyengar; Venkatesh Rajagopalan (Centre For Tourism Planning and Development, 2019)
Abstract. There is a remarkable change in the thought process of Indian families - in the last few years regarding the way they live their life. How they socialize with their near & dear ones and most importantly how they spend their holidays. Indian families started focusing on the big picture and that is how they are becoming more open and adaptive to change. Vacation is one such thing in which all the members give their inputs on how, where to go. They do justify their reasons for selecting a destination based on their perspective, which can be a comforting one to them individually. Vacations by Indian families are on the rise year by year. Reasons may be with higher levels of income, stress, boredom, disposable income, increasing percentage of working couples and better knowledge of destinations. All these and many more have contributed to the upsurge of Indian vacationers. Having said that, the question remains as to how they decide when and where to go on vacation and what are the factors contributing to the decision. This is a study aimed at identifying the factors and how a decision is arrived at given the constraints. This paper also hopes to provide a decision-making tree that can be used as a readily reckoned by Indian families - when deciding on a vacation. Along with listing multiple factors that go into making a decision. The scope for this study is families based out of Chennai and the kind of vacations they undergo and cherish.